Preparation of snack with machica flour and nuts to combat malnutrition in Monte Sinai Educational Unit in Guayaquil-Ecuador - Gordillo Alvarado, Mercedes; Viteri Carrillo, Tatiana Priscila (Ingeniería Química y Desarrollo, 2022)
The purpose of this titling work is to prepare a snack with machica flour and nuts to combat malnutrition in vulnerable areas of Guayaquil-Monte Sinaí, being the main problem the lack of knowledge in giving the first nutritional collation, machica was included as an ingredient Main in snack making, these were distributed in the Monte Sinaí Guayaquil Educational Unit. Its methodological approach was based on the quantitative method, it was also directed under the experimental method where study tests were carried out on the selected products such as: machica flour and nuts (almond and walnut). The study population was composed of 95 children who start from 5-10 years of age, belonging to the Educational Unit already exposed. As a result, the initial general average weight of 17.2 ± 4.0323 was obtained. Putting into practice the proposal of this work (Snack of machica flour and dried fruits-balanced diet) new measures were taken in the current weight-size, where the data show that the average weight gained corresponds to 0.52173913 ± 0.338626551. Also, in what corresponds to the size, it is stated that the initial average size is 121.6195 ± 11.040; In consideration of the average size of the first month of the trial in terms of the proposal (biscuit of machica flour and nuts-balanced diet according to the requirements) it was evidenced that it is 122.54 ± 11.24. As a result, it was concluded that the balanced diet and the nutritious cookie had a positive impact on children's nutrition
Keywords: Malnutrition; Snack; Flour; Dried Fruit; Healthy Food